Antibiotic Use and Childhood Body Mass Index Trajectory - Schwartz, Brian S. (Int J Obes (Lond), 2015)
BACKGROUND/OBJECTIVES: Antibiotics are commonly prescribed for children. Use of antibiotics early in life has been linked to weight gain but there are no large-scale, population-based, longitudinal studies of the full age range among mainly healthy children. SUBJECTS/METHODS: We used electronic health record data on 163,820 children aged 3-18 years and mixed effects linear regression to model associations of antibiotic orders with growth curve trajectories of annual body mass index (BMI) controlling for confounders. Models evaluated three kinds of antibiotic associations – reversible (time-varying indicator for an order in year before each BMI), persistent (time-varying cumulative orders up to BMI(j)), and progressive (cumulative orders up to prior BMI [BMI(j-1)]) – and whether these varied by age. RESULTS: Among 142,824 children under care in the prior year, a reversible association was observed and this short-term BMI gain was modified by age (p < 0.001); effect size peaked in mid-teen years. A persistent association was observed and this association was stronger with increasing age (p < 0.001). The addition of the progressive association among children with at least three BMIs (n = 79,752) revealed that higher cumulative orders were associated with progressive weight gain; this did not vary by age. Among children with an antibiotic order in the prior year and at least seven lifetime orders, antibiotics (all classes combined) were associated with an average weight gain of approximately 1.4 kg at age 15 years. When antibiotic classes were evaluated separately, the largest weight gain at 15 years was associated with macrolide use. CONCLUSIONS: We found evidence of reversible, persistent, and progressive effects of antibiotic use on BMI trajectories, with different effects by age, among mainly healthy children. The results suggest that antibiotic use may influence weight gain throughout childhood and not just during the earliest years as has been the primary focus of most prior studies.